2015
DOI: 10.1016/j.vaccine.2015.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Generation of switched memory B cells in response to vaccination in Down syndrome children and their siblings

Abstract: Down syndrome individuals should be considered a high risk group, because of their increased susceptibility to infection and reduced number of switched memory B cells. Tailored vaccination protocols are needed in order to reduce their burden of infections throughout life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…There is conflicting evidence regarding serum immunoglobulin levels in DS. Valentini et al (30) found that overall serum immunoglobulin levels were in the normal range, except for IgA which was found to be 40% lower compared with controls. They also found that salivary IgA was normal, despite the contrary being reported in other studies (31).…”
Section: B Lymphocytesmentioning
confidence: 95%
“…There is conflicting evidence regarding serum immunoglobulin levels in DS. Valentini et al (30) found that overall serum immunoglobulin levels were in the normal range, except for IgA which was found to be 40% lower compared with controls. They also found that salivary IgA was normal, despite the contrary being reported in other studies (31).…”
Section: B Lymphocytesmentioning
confidence: 95%
“…Following vaccination to influenza A or polysaccharide pneumococcus, antibody responses are active in persons with Down syndrome, yet antibody titres are lower [166,169,177,178]. One possible contribution to increased prevalence and severity of pulmonary infection in Down syndrome could be reduced numbers of subsets of B-cells, such as switched memory B-cells [179,180]. Deficit of such cells in Down syndrome could result in suboptimal protection from, and response to, infectious agents.…”
Section: Immune System Disturbances Impacting Cardiopulmonary Functiomentioning
confidence: 99%
“…IgM memory B cells representing the first-line defense against infection [10] are 1/3 of normal, whereas highly specific switched memory B cells are 7-10 fold less than expected [11,12]. We have also shown that children with DS respond poorly to primary immunization and their protection may require tailored vaccination protocols [13].…”
Section: Introductionmentioning
confidence: 65%
“…Notwithstanding the numerous reports demonstrating that immune deficiency is a consistent feature of the syndrome, [14] children with DS are not included in the list of patients at higher risk for infection. We suggest that pneumococcal and influenza vaccines should be strongly considered in children with DS [13]. In addition, Palivizumab for RSV prophylaxis is indicated for DS children with congenital heart disease or prematurity.…”
Section: Discussionmentioning
confidence: 99%